Subfoveal choroidal thickness in retinitis pigmentosa cases [Retinitis pigmentoza olgularinda subfoveal koroid kalinligi] - (:unkn) unknown (Gazi Eye Foundation, 2017)
Purpose: To evaluate the subfoveal choroidal thickness in retinitis pigmentosa cases and to assess its relationship with visual acuity. Materials and Methods: The central, temporal and nasal subfoveal choroidal thickness was measured with the EDI software of spectral domain optic coherence tomography (OCT) RTVue 100 5.1 (Optovue Inc. Fremont, Canada) Results: The choroidal thickness results of 48 cases diagnosed with retinitis pigmentosa and 37 healthy individuals were compared. The central, temporal and nasal subfoveal choroidal thickness in retina pigmentosa patients were significantly thinner than the healthy controls. (p< 0.001, all). Visual aquities did not show any corelation with the choroidal thickness at nasal, temporal and macular area. Conclusion: The choroidal thickness results of 48 cases diagnosed with retinitis pigmentosa and 37 healthy individuals were compared. The central, temporal and nasal subfoveal choroidal thickness in retinitis pigmentosa patients were significantly thinner than the healthy controls. (p< 0.001, all). The subfoveal choroidal thickness in three regions were observed no correlation between the visual acuity. © 2017 Gazi Eye Foundation. All rights reserved.
Keywords: Choroidal thickness; Retinitis pigmentosa